The importance of specialization training and opportunities to utilize the qualifications of specialists in long-term care nursing to improve the quality of nursing care of chronically and terminally ill patients - Kądalska, Ewa; Żmuda-Trzebiatowska, Halina; Pawłowska, Katarzyna (Nursing in the 21st Century, 2016)
THE IMPORTANCE OF SPECIALIZATION TRAINING AND OPPORTUNITIES TO UTILIZE THE QUALIFICATIONS OF SPECIALISTS IN LONG-TERM CARE NURSING TO IMPROVE THE QUALITY OF NURSING CARE OF CHRONICALLY AND TERMINALLY ILL PATIENTS Aim of the Study. To analyse the usefulness of specialization training in the area of long-term care nursing as well as the possibilities to make use of the acquired qualifications – in the opinion of the specialists in this area. Material and Methodology. The questionnaire survey was conducted among 162 specialists in long-term care nursing. Results. The majority of respondents considered the specialization training as useful (91.4%) and meeting their expectations (83.9%). As the result of obtained specialization, they perform their work with patients better (67.9%), demonstrate expertise and proficiency as well as high degree of efficiency (67.3%). Some of them exercise their right to independent provision of healthcare services, predominantly the assessment of the patient’s level of consciousness with the use of methods and classifications (75.7%), physical examination (61.2%), oxygen therapy (55.3%), and definitely less often – referral to diagnostic tests (20.4%). Conclusions. Completion of a specialization training in the area of long-term care nursing brings satisfaction and professional prestige to specialists, results in increased professional independence and improvement in the quality of provided care. However, high qualifications of this professional group are underutilized.